Comparative effects of valsartan plus either cilnidipine or hydrochlorothiazide on home morning blood pressure surge evaluated by information and communication technology–based nocturnal home blood pressure monitoring. Issue 1 (5th January 2018) - Fujiwara, Takeshi; Tomitani, Naoko; Kanegae, Hiroshi; Kario, Kazuomi
Abstract: The authors tested the hypothesis that a valsartan/cilnidipine combination would suppress the home morning blood pressure (BP) surge (HMBPS) more effectively than a valsartan/hydrochlorothiazide combination in patients with morning hypertension, defined as systolic BP (SBP) ≥135 mm Hg or diastolic BP ≥85 mm Hg assessed by a self‐measuring information and communication technology–based home BP monitoring device more than three times before either combination's administration. This was an 8‐week prospective, multicenter, randomized, open‐label clinical trial. The HMBPS, which is a new index, was defined as the mean morning SBP minus the mean nocturnal SBP, both measured on the same day. The authors randomly allocated 129 patients to the valsartan/cilnidipine (63 patients; mean 68.4 years) or valsartan/hydrochlorothiazide (66 patients; mean 67.3 years) combination groups, and the baseline HMBPS values were 17.4 mm Hg vs 16.9 mm Hg, respectively ( P  =   .820). At the end of the treatment period, the changes in nocturnal SBP and morning SBP from baseline were significant in both the valsartan/cilnidipine and valsartan/hydrochlorothiazide groups ( P  <   .001): −5.0 vs −10.0 mm Hg ( P  =   .035) and −10.7 vs −13.6 mm Hg ( P  =   .142), respectively. HMBPS was significantly decreased from baseline in both groups ( P  <   .001), but there was no significant difference between the two groups: 14.4 mm Hg vs 14.0 mm Hg, respectively ( P  =   .892). Valsartan/cilnidipine could not significantly suppress HMBPS compared with valsartan/hydrochlorothiazide. Large‐scale randomized controlled studies are needed to assess how reducing HMBPS will affect future cardiovascular outcomes. The information and communication technology–based home BP monitoring device may become an alternative to ambulatory BP monitoring, which has been a gold standard to measure nocturnal BP and the morning BP surge.